Anisotropy and humidity effect on tensile properties and electrical volume resistivity of fused deposition modeled acrylonitrile butadiene styrene composites - Almenara Cueto, Carlos Ignacio (2017)
In the present thesis, the influence of anisotropy and humidity in the tensile properties and electrical volume resistivity of Acrylonitrile Butadiene Styrene/Carbon Nanotubes and Acrylonitrile Butadiene Styrene/Micro Carbon Fibers manufactured by Fused Deposition Modeling 3D printing was studied. To study the influence of the anisotropy three different layer printing orientations were compared (0°, 45° and 45°/-45°) in a layer height of 0.2 mm. It was concluded that the influence of anisotropy is important on Acrylonitrile Butadiene Styrene/Micro Carbon Fibers tensile behavior due to relation that exist between the performance/resistance and the alignment of the reinforcement. On the other hand, no significant influence was found on the Acrylonitrile Butadiene Styrene/Carbon Nanotubes. On the electrical volume resistivity, no significant variation was found on the Acrylonitrile Butadiene Styrene/Carbon Nanotubes by the anisotropy of the layers. Acrylonitrile Butadiene Styrene/Micro Carbon Fibers could not be essayed because of the high resistance of the composite.